Ampicillin and Gentamicin Are a Useful First-line Combination for the Management of Sepsis in Under-five Children at an Urban Hospital in Bangladesh (Journal of Health, Population and Nutrition, 2013)
The study evaluated the commonly-used drugs for the management of sepsis and their outcome among under-five children. We evaluated the hospital-records of all paediatric sepsis patients (n= 183) in the intensive care unit (ICU) and longer-stay unit (LSU) of the Dhaka Hospital of icddr,b. These records were collected from the hospital management system (SHEBA) during November 2009 to October 2010. A total of 183 under-five children with clinical sepsis were found during the study period, and 14 (8%) of them were neonates. One hundred and eighty-one patients had received a combination of injection ampicilin and injection gentamicin, and two patients had received the combination of injection ceftriaxone and injection gentamicin. Only 46 (25%) patients required a change of antibiotics to the combination of intravenous ceftriaxone plus gentamicin after non-response of injection ampicilin and injection gentamicin combination; 7/181 (4%) patients died who received injection ampicilin and injection gentamicin whereas none died among the other two patients who received injection ceftriaxone and injection gentamicin (p=1.00). The combination of injection ampicilin and injection gentamicin as the first-line antibiotics for the management of sepsis in children even beyond the neonatal age is very effective, resulting in lower mortality. DOI: http://dx.doi.org/10.3329/jhpn.v30i4.13418 J HEALTH POPUL NUTR 2012 Dec;30(4):487-490